39.2k views
5 votes
Simplify 6z^-7 (2) x² (4) ^4x^-4​

User Paridokht
by
5.4k points

2 Answers

5 votes

Explanation:

First, subtract

7

from each side of the equation to put the equation in standard form:

x

2

+

4

x

+

4

7

=

7

7

x

2

+

4

x

3

=

0

We can now use the quadratic formula to find the solutions for

x

. The quadratic formula states:

For

a

x

2

+

b

x

+

c

=

0

, the values of

x

which are the solutions to the equation are given by:

x

=

b

±

b

2

(

4

a

c

)

2

a

Substituting:

1

for

a

4

for

b

3

for

c

gives:

x

=

4

±

4

2

(

4

1

3

)

2

1

x

=

4

±

16

(

12

)

2

x

=

4

±

16

+

12

2

x

=

4

±

28

2

x

=

4

±

4

7

2

x

=

4

±

4

7

2

x

=

4

±

2

7

2

x

=

4

2

±

2

7

2

x

=

2

±

7

Or

x

=

2

+

7

and

x

=

2

7

User Joseph Ireland
by
5.9k points
4 votes

Answer:

3

Explanation:

User Jorge Machado
by
5.9k points